The effect of exopolysaccharides from EMS-induced Porphyridium cruentum mutant on human epidermal and dermal layers - Han, Sang-Il; Heo, Young Mok; Jeon, Min Seo; Kyung, Seoyeon; Kang, Seunghyun; Kwon, Soon-Jae; Ryu, Jai Hyunk; Kim, Jae Hoon; Ahn, Joon-Woo (Frontiers in Marine Science, 2024)
Introduction Microalgae biotechnology utilizes species like Porphyridium cruentum for their valuable phycobiliproteins and exopolysaccharides, which have potential industrial applications and health benefits, particularly in skin condition improvement. Methods A mutant of P. cruentum LIMS-PS-1061 was developed through ethyl methanesulfonate mutagenesis and subsequent colony screening to study changes in its biomass production and pigment composition under different lighting conditions. Results and discussion The mutant exhibited a 33.9% increase in dry weight under white light compared to the wild type. Despite maintaining the total pigment content, specific components changed significantly: chlorophyll content decreased 2.20- and 3.61-fold under white and blue light respectively, while phycobiliproteins increased 1.59- and 1.23-fold under the same conditions. These alterations suggest a compensatory mechanism for maintaining photosynthetic capacity. Furthermore, the exopolysaccharides of P. cruentum upregulated genes related to skin moisturization, barrier enhancement, and elasticity, and promoted wound healing through fibroblast migration. This supports the proposed mechanism of action for P. cruentum’s exopolysaccharides in improving human skin conditions by integrating the effects of aquaporin 3, filaggrin, involucrin, loricrin, elastin, and fibrillin-1.